Cardiometabolic profiles in women with adenomyosis. (3rd October 2022) - Ates, Seda; Aydın, Serdar; Ozcan, Pinar
Abstract: The aim of this study was to investigate the reproductive profiles, metabolic parameters and cardiometabolic risk assessed by surrogate indexes in women with adenomyosis. Ninety-six premenopausal women who were diagnosed with adenomyosis by transvaginal ultrasound and 97 age-body mass index (BMI) matched controls with normal ultrasound during routine examination were included. Women with adenomyosis were more likely to have higher gravidity and had more abortions than women without adenomyosis. Regarding the individual metabolic syndrome components, the adenomyosis group was more likely to have higher prevalence of hypertension, low HDL-C and central obesity. No significant difference was found between the groups in terms of visceral adiposity index, lipid accumulation product and fatty liver index. Only higher blood pressure (BP) remained statistically significant after adjustment for confounding factors in multivariate analysis. Women with adenomyosis had remarkably high risk of hypertension. It may be advisable to monitor their BP closely. Impact Statement: What is already known on this subject? The only anthropometric characteristic assessed in women in relation to adenomyosis is body mass index (BMI). A case-control study showed that women who are obese are more likely to have adenomyosis. The gravidity, number of spontaneous abortions and previous uterine surgeries such as dilatation and curettage (D&C) and caesarean section were found significantly associated with adenomyosis. What do the results of this study add? A remarkable finding of our study was the increased incidence of higher systolic BP in women with adenomyosis. No difference was observed in adiposity indices between women with and without adenomyosis. Higher prevalence of central obesity and lower HDL-C levels were seen in women with adenomyosis. What are the implications of these findings for clinical practice and/or further research? The study identifies that adenomyosis is associated with an increased risk of hypertension, and women with adenomyosis may be monitored closely for blood pressure changes. Our report also provides novel information about the metabolic risk profiles associated with adenomyosis.